Identification of Port Calls Based on AIS Messages Analysis - Maciaszek, Adam; Małyszko, Jacek; Stróżyna, Milena (Studia Oeconomica Posnaniensia, 2017)
The article concerns the issue of the identification of port calls based on data retrieved from the AIS system. Such identifi cation may play an important role in increasing maritime awareness, for example for the needs of coast guards. In the article we discuss experiments, which were performed and based on data from the AIS system as well as from the MarineTraffic.com portal, where the latter data was used for the purpose of the evaluation of the proposed method of port calls identifi cation. Th e experiments showed that the development of reliable data collection is vital if further research in this area is to be performed.